Emotional Intelligence and Extra-Role Behavior of Knowledge Employees: Mediating and Moderating Effects - Yu, Huajiang; Takahashi, Yoshi (Organizations and Markets in Emerging Economies, 2020)
This study constructed a model to explore how emotional intelligence (EI) predicts organizational citizenship behavior (OCB) and counterproductive work behavior (CWB) via the mediators of job satisfaction (JS) and work engagement (WE). Furthermore, this study examined whether organizational justice (OJ) and person-organization fit (P-O fit) moderate the effect of EI on OCB and CWB. The model was tested using data from 540 knowledge employees in mainland China. This study found that JS and WE positively and partially mediated the association between EI and OCB, as well as negatively and partially mediated the association between EI and CWB. Moreover, OJ and P-O fit moderated the effect of EI positively on OCB and negatively on CWB. This study revealed the mechanism from EI to OCB and CWB through multiple mediators, identified two variables that may adjust EI-OCB and EI-CWB relationships, and proposed that organizations could promote OCB and diminish CWB of knowledge employees by employing certain human resource practices.
Keywords: emotional intelligence; knowledge employees; organizational citizenship behavior; counterproductive work behavior; mediation; moderation